PENGARUH KEPEMIMPINAN TRANSFORMASIONAL, STRES KERJA, DAN KEPUASAN KERJA TERHADAP TURNOVER INTENTION - Inni Dian Rohani; Dwi Nita Aryani (POLITEKNIK LP3I JAKARTA, 2025)
Transformational leadership style can increase employee motivation and job satisfaction. Job stress has the potential to decrease employee satisfaction and increase intention to leave the company. Job satisfaction can be a determining factor in retaining employees to remain committed to the organisation. This study aims to analyse the effect of transformational leadership style, job stress, and job satisfaction on turnover intention; as well as the role of stress and job satisfaction as intervening variables. This type of research is quantitative by distributing questionnaires to employees of Public Company Jasa Tirta I, with a sample of 109 people. Regression test to see the direct effect between variables and mediation test to determine the role of job satisfaction and job stress in mediating the effect of transformational leadership on turnover intention. The results showed that transformational leadership style has a positive effect on job satisfaction and a negative effect on turnover intention. Job stress has a positive effect on turnover intention, while job satisfaction has a negative effect on turnover intention. Job satisfaction and job stress act as significant mediating variables in the influence between transformational leadership and turnover intention. The implication of this study is that companies need to implement effective transformational leadership to increase job satisfaction and reduce turnover intention. Good management of job stress is necessary to retain employees in the long term.